Eksistensi Klausula Non Kompetisi dalam Perjanjian Waralaba untuk Mencegah Persaingan Usaha Tidak Sehat - Etty Indrawati (JURNAL YUSTIKA: MEDIA HUKUM DAN KEADILAN, 2023)
A Franchise Agreement is a written agreement between Franchisor and Franchisee. The Franchise Agreement may contain provisions in which the franchisor requires the franchisee not to carry out the same business activities as the ongoing franchise businesses for a certain period after the expiration of the franchise agreement (non-competition clause). In practice, there were unscrupulous franchisees with bad intentions, establishing franchise partnerships with franchisors to get the know-how provided by the franchisor; then, before or after the end of the franchise agreement immediately setting up the same business/ potentially becoming a business competitor to the franchisor. There are two purposes of this article. The first is to explore and analyze the importance of the non-competition clause in franchise agreement/ the risk if the non-competition clause is not included/ not stipulated in franchise agreement. The second is to investigate how to arrange the non-competition clause in a franchise agreement to prevent unfair business competition. This research project uses qualitative method, involves respondents and informants from business owners of national franchisors. There are two results of this study. The first is the non-competition clause in franchise agreement is very important and risky if the non-competition clause is not included in franchise agreement. This is because if the franchisor's business system is adopted by other parties, it will be detrimental to the franchisor who has built his business from scratch. The second is the non-competition clauses in franchise agreements should bind the franchisee's person, location and apply post contractually. This provision remains in force and must be complied with by the franchisee (within a certain period) even if the franchise agreement has ended. The research results are expected to provide a reference and understanding of the parties’ interests in the franchise agreement that need to be secured, particularly regarding intellectual property rights and the transfer of know-how, which must be respected to prevent unfair business competition by business actors. This research is expected to provide input to KPPU regarding breaches of the non-competition clause in franchise agreements that have the potential to qualify as acts of unfair business competition.